Virtual Socializing and Nonlinear Effects on Victimization - Boccio, Cashen M. (Journal of interpersonal violence, 2023)
Previous research documents relationships between unstructured socializing activities and in-person victimization in adolescents. In parallel, there is a body of research which has linked virtual socialization activities (i.e., social networking, texting, video chatting, phone usage) with both online and in-person victimization. The majority of research in this area, however, has assumed the relationship between time spent engaging in virtual socializing and victimization is linear. Yet, there are several reasons to anticipate that while virtual socializing may initially increase the risks for in-person victimization, after adolescents begin spending a significant portion of their free time socializing virtually this may function to displace time they would have otherwise spent engaging in unstructured socializing in-person. As a result, very high levels of engagement in virtual socializing may actually lower the risks for in-person victimization. This study addresses this gap in the literature by utilizing negative binomial regression and logistic regression to test for nonlinearity in the relationship between virtual socializing and three forms of in-person victimization (i.e., violent, property, and in-person bullying) using data from the 8th and 10th grade 2018 cohort of Monitoring the Future. In addition, this study tests for nonlinearity in the relationship between virtual socializing and one form of online victimization (i.e., cyberbullying). Our findings reveal that virtual socializing is associated with all four forms of victimization. In addition, tests for nonlinearity revealed that virtual socializing exhibits a nonlinear relationship with in-person property victimization and cyberbullying victimization. Additional analyses revealed differential relationships between individual virtual socializing activities and the risks for property victimization. On the other hand, three out of the four forms of virtual socializing activities were found to exhibit nonlinear relationships with the likelihood of cyberbullying victimization. Overall, these findings imply that virtual socializing activities appear to exhibit nonlinear relationships with several forms of victimization.